2005
DOI: 10.1002/ijc.21459
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus type 18 E6 and E7‐specific CD4+ T‐helper 1 immunity in relation to health versus disease

Abstract: The most common high-risk human papillomavirus types, HPV16 and 18, differ markedly with respect to their interaction with the host. Clearance of HPV18 infections generally takes longer and HPV18-positive cancers have a poorer prognosis. We therefore evaluated Th1-type immunity against the E6 and E7 oncoproteins of HPV18 in healthy subjects and in patients with HPV18-positive genital cancer, and compared the results to our previously obtained data for HPV16. Approximately 20% of the healthy individuals display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 21 publications
3
61
1
4
Order By: Relevance
“…By in vitro studies, we previously identified promiscuous HPV-18 E6 CD4 epitopes recognized by 18% of healthy donors (15). Similar frequencies were found in another study (16), in which no reactivity in cervical cancer patients was found.…”
supporting
confidence: 77%
“…By in vitro studies, we previously identified promiscuous HPV-18 E6 CD4 epitopes recognized by 18% of healthy donors (15). Similar frequencies were found in another study (16), in which no reactivity in cervical cancer patients was found.…”
supporting
confidence: 77%
“…The immune responses of the host against HPV antigens eliminate most of the infections and promote lesion regression, probably through a CD4 Th1 response against the proteins E2, E6, and E7 (13). Interestingly, women bearing HPV-associated tumors not only have weak CD4 responses (13,14), but also display regulatory ones from lymphocytes stimulated with HPV antigens (15). In addition, a positive correlation was found between the number of CD68 + macrophages in cervical disease and lesion grade (16,17).…”
mentioning
confidence: 99%
“…12 The exact component of the adaptive immune system responsible for regression of HR HPV infection remains unclear, with CD4 responses to viral non-structural proteins the most likely candidates. 13 Also surprisingly, cervical pre-cancer is a much earlier and commoner complication of acute infection with high risk HPVs in younger women than had been predicted, with a significant incidence as early as two years after primary infection. 8 Reconciling these data with a prior linear model of progression of HPV infection to cancer over decades, and with the observed frequency of pre-cancer in older screened populations, has led to significant shifts in the paradigms concerning HPVs role in initiating cervical pre-cancer.…”
Section: Delivering Papillomavirus Vaccines When and Where They're Momentioning
confidence: 98%